Differences in trunk rotation during baseball batting between skilled players and unskilled novices - Hiroki Nakata; Akito Miura; Michiko Yoshie; Takatoshi Higuchi; Kazutoshi Kudo (Japanese Society of Physical Fitness and Sports Medicine, 2014)
We investigated differences in trunk rotation patterns during baseball batting in eight skilled (collegiate level) players and nine unskilled novices using high-speed video cameras. The maximum angle during the backswing, angle at bat-ball impact, and angular displacement during the forward swing were analyzed for data on upper torso, pelvis, and torso-pelvis interaction (trunk twist) angles. We also noted movement variability in these angles over 10 trials, which was calculated as the standard deviation. The timing of the maximum angle during the backswing and variability was also analyzed. Statistical analysis revealed that angular displacements in the upper torso, pelvis, and torso-pelvis interaction were significantly larger in skilled players than in unskilled novices (p < 0.001, p < 0.001, and p < 0.05, respectively). The timing of the maximum pelvis angle during the backswing was significantly later in skilled players than in unskilled novices (p < 0.05). Movement variability in angular displacement during the forward swing and timing during the backswing were significantly greater in unskilled novices than skilled players. Although many previous studies reported the importance of angular velocity in trunk rotation during baseball batting, our results indicate that angular displacement and movement variability during trunk rotation are also key components for understanding the proficiency of skilled baseball players and unskilled novices.